Relationship between Type of Feeding and Duration of Hospitalization of Infants Admitted for Diarrhea in Babylon Maternity and Paediatrics Teaching Hospital (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: Breast milk is considered the best type of feeding for infants. WHO recommends exclusive breastfeeding for 6 months, and the continuation of breastfeeding for up to 2 years of age. It has a role in reducing morbidity and mortality of diarrhea. In Iraq, diarrheal diseases are considered 2nd most common cause of mortality among children, therefore, promotion of breast-feeding may help reduce diarrhea in Iraq.Aim of the Study: To identify the type of feeding in patients with diarrhea, and to assess the relationship between the type of feeding and the duration of hospitalization for infants admitted for diarrhea in Babylon Maternity and Paediatrics Teaching Hospital.Patients & Methods: This study is an observational analytical study conducted in Babylon Maternity And Paediatrics Teaching Hospital during the period from April 2018 through June 2018 and included information from a 96 pediatric patients admitted in the aforementioned hospital for diarrhea. Patients' exposure to breast milk was assessed as well as other characteristics.Results: Study included a total of 96 patients with age ranging from days up to 36 months. Linear regression has shown a significant difference in duration of hospitalization among those who are breastfed and those who are not, t=1.42, P-value=0.001.  ANOVA demonstrated a significant relationship between dehydration level and duration of hospitalization. Student’s t-test has shown a significant relationship between water source and the duration of hospitalization (P-value = 0.012).Conclusion: There is a significant relationship between breastfeeding and the duration of hospitalization of diarrhea patients when adjusted for age group and sex. Also there is a strong relationship between source of water and duration of hospitalization. Similarly, there is a significant correlation between severity of dehydration and the duration of hospitalization.